Economic Efficiency of Mango Cultivator in The Southern Vietnam - et. al., Truong Hong Vo Tuan Kiet, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The paper employed a Cobb-Douglas and translog of stochastic frontier profit function to measure the level of economic efficiency and its determinants. Structured questionnaires were used to collect data from 1,889 of sampling observations (591 for season 1, 678 for season 2, and 620 for season 3) randomly selected from designated locations in the study area. Difference of the study compared to past researches related to tropical fruits analyzed efficiency of three seasons instead of only focusing on efficiency of one season or total a year. The study established a mean economic efficiency of 26.19% in season 1, 27.15% in season 2, and 24.62% in season 3. The paper found out positive determinants of economic efficiency were farming experience, wrapping bag, market access among three seasons; education in season 1 and plant density in season 1 and 2. By contrast, the constraints to profit of mango producers were age, and payment for agro-input wholesale on ending of season in three seasons; credit access and classifying sale in first and second seasons; education in second and third seasons; plant density in season 3. Based on these findings, policy makers should focus on effective inputs models that would boost profit efficiency through conducting regular workshops and orchard demonstrations on using input materials effectively. More so, farmers should design mango gardens with appropriate trees density as well as encourage gardeners to use bags for wrapping mango fruits in farming in order to increase economic efficiency.